Sliding mode control based impact angle control guidance considering the seeker׳s field-of-view constraint. (March 2016) - Wang, Xingliang; Zhang, Youan; Wu, Huali
Abstract: The problem of impact angle control guidance for a field-of-view constrained missile against non-maneuvering or maneuvering targets is solved by using the sliding mode control theory. The existing impact angle control guidance laws with field-of-view constraint are only applicable against stationary targets and most of them suffer abrupt-jumping of guidance command due to the application of additional guidance mode switching logic. In this paper, the field-of-view constraint is handled without using any additional switching logic. In particular, a novel time-varying sliding surface is first designed to achieve zero miss distance and zero impact angle error without violating the field-of-view constraint during the sliding mode phase. Then a control integral barrier Lyapunov function is used to design the reaching law so that the sliding mode can be reached within finite time and the field-of-view constraint is not violated during the reaching phase as well. A nonlinear extended state observer is constructed to estimate the disturbance caused by unknown target maneuver, and the undesirable chattering is alleviated effectively by using the estimation as a compensation item in the guidance law. The performance of the proposed guidance law is illustrated with simulations. Abstract : Highlights: An impact angle control guidance law with seeker׳s field-of-view constraint is designed based on the sliding mode control theory. A time-varying sliding surface that guarantees zero miss distance and zero impact angle error without violating the seeker׳s field-of-view constraint is constructed. A reaching law is designed to enforce the occurrence of sliding mode in finite time by using a control integral barrier Lyapunov function. No additional switching logic is used to maintain the seeker׳s lock-on condition, and hence no abrupt-jumping of guidance command is experienced. The proposed guidance law can be used to intercept maneuvering targets.